PENYULUHAN NUTRISI SEIMBANG UNTUK PENCEGAHAN STUNTING PADA ANAK DI BANJAR JAGATAMU, DESA MELILING, TABANAN - I Gusti Ayu Prema Yani Sideme; Ida Ayu Mirah Agung; I Made Benni Labba P. (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Stunting is still one of the unresolved child health problems in Indonesia. Education related to providing balanced nutrition is one of the critical keys to preventing stunting in children. We conducted a pediatric health education program regarding "Balanced Nutrition to Reduce Stunting" in Banjar Jagatamu, Meliling Village, Kerambitan, Tabanan on November 17, 2024. This education involved residents of Banjar Jagatamu. We used an educational approach and involved various interactive activities during counseling. During counseling, we provided education regarding nutritional needs according to the child's age, the importance of a high-protein diet for children aged 6 to 24 months, and the importance of routine monitoring of child growth and development at primary health care for early detection of stunting. During the counseling, participants listen enthusiastically and actively ask questions during the discussion session. In addition to increasing participants' insight, this education regarding a balanced diet for children could be a sustainable stunting prevention strategy so that the community and health workers can work together to accelerate reducing stunting in Indonesia